The use of neoprene fabric evaluation in terms of comfort in child tracksuit production - (:unkn) unknown (INST NATL CERCETARE-DEZVOLTARE TEXTILE PIELARIE-BUCURESTI, 2018)
Neoprene fabric. which used in the manufacture of diving, wind surfing and fishing clothes, made a rapid entry into the fashion industry. This fabric is resistant to petroleum products, water and wind. At the same time it is also resistant to temperatures between -50 degrees C and +120 degrees C. It has been used in daily wear because of the flexible structure. In this study. neoprene fabrics having different properties are compared in terms of comfort and physical properties in order to determine whether a neoprene fabric is suitable in the child tracksuit production.
Keywords: neoprene; knitted fabrics; functional clothing; thermal comfort; motion comfort